QUASI-VERTICAL INTEGRATION MODEL IN PARTNERSHIP OF SMES (SMALL MEDIUM ENTERPRISES) AND THE ROLE OF COMPETITION COMMISSION IN EU AND INDONESIA - Hernayanto, Yayan; Toha, Kurnia; Silalahi, Udin (Indonesia Law Review, 2024)
Partnerships between large and small companies should not be imagined as David and Goliath, enemies of each other. However, partnerships between large and small business actors are a mutually beneficial synergy. Partnerships with Small and Medium Enterprises (SMEs) are not charity activities that prevent them from growing strongly. Guidance and assistance need to be provided so that they grow with a strong foundation. Both parties must agree to a fair transaction scheme, trade terms, and clauses that sustain this partnership and not cause SMEs to go bankrupt. Quasi-Vertical Integration is a model for conducting transactions in the manufacturing industry. This article is compiled using a doctrinal research method, namely analyzing the implementation of partnership regulations in Indonesia in the context of partnerships with the Automotive Industry (OEM), as well as examining the role of the Competition Supervisory Commission (KPPU) in Indonesia, which has been given the authority to oversee this partnership. More specifically, this article discusses and presents several points: first, how good partnership protection in Indonesia and the EU protects SME businesses; second, how the partnership pattern of SMEs in the automotive sector between Quasi-Vertical integration and quasi-rent is implemented as Vertical Integration; Finally, how the KPPU in Indonesia uses its authority in considering supervising partnerships and its comparison with the EU. As a conclusion in this article, mandatory partnerships in Indonesia are implemented based on the OSS (Online Single Submission) requirements in the registration or licensing of investment. Voluntary Partnerships are agreements between Parties that are equal with the principle of mutual need and mutual benefit. The partnership pattern of SMEs in the automotive sector between Quasi-Vertical integration and quasi rent is implemented as Vertical Integration which is not prohibited by Indonesian competition law. KPPU must encourage voluntary partnerships by Business Actors and SMEs as a more appropriate approach to developing Partnerships